Commodity Prices and the Dynamics of Inflation in Commodity-exporting Nations: Evidence from Australia and Canada - Bloch, Harry; Dockery, Alfred Michael; Sapsford, D. (Economic Society of Australia, 2005)
A commodity price boom is under way. What does this boom mean for countries with substantial net commodity exports? In particular, can a commodity price boom be expected to increase inflationary pressure on the domestic economy?Because primary commodities are standardized and traded globally, price increases impact on all countries given the prevailing foreign exchange rates. This creates upward pressure on finished goods prices, as the direct costs of production, including raw material costs are marked up to determine finished goods prices. The behaviour of finished goods prices then depends on domestic movement in wage rates, labor productivity and price-cost margins.Both the Australian and Canadian dollars are viewed as "commodity currencies", implying co-movement of the exchange rate with the commodity prices. In particular, currency appreciation with rising commodity prices can offset the impact of global commodity prices on domestic raw material costs. Thus, an exchange-rate equation is included in our small structural model for inflation determination in Australia and Canada. The full model includes equations for the world price of primary commodities, the foreign exchange rate, the domestic price of finished goods and domestic industrial wages. We estimate this model using quarterly data covering 1960 through 2001. The results show evidence that the world commodity price boom increases inflation in both Australia and Canada, albeit with an influence that is moderated by the partially offsetting impact of exchange rate appreciations (depreciations) during commodity price booms (busts).